On line graphs of bipartite graphs - Staton, William; Wingard, G. Clifton (Utilitas Mathematica, 1998)
Two characterizations of line graphs of bipartite graphs are presented. One involves a set of forbidden subgraphs. The other is related to the chessboards in the theory of rook polynomials.